Automated tool for 3D planar magnetic temperature modelling: application to EE and E/PLT core‐based components. Issue 15 (7th November 2019) - Bakri, Reda; Margueron, Xavier; Ngoua Teu Magambo, Jean Sylvio; Le Moigne, Philippe; Idir, Nadir
Abstract : Thermal performance of power converters is a key issue for the power integration. Temperatures inside the active and passive devices can be determined using thermal models. Modelling the temperature distribution of high‐frequency magnetic components is quite complex due to the diversity of their geometries and used materials. This study presents a thermal modelling method based on lumped elements thermal network model, applied to planar magnetic components made of double planar E shaped cores (EE) and planar E core combined with plate one (E/PLT). The 3D model is automatically generated from the component's geometry. The computation enables to obtain 3D temperature distribution inside windings and core of planar transformers or inductors, in steady state or in transient case. This study details the proposed modelling method as well as the automated tool including the problem definition and the solving process. The obtained temperature distributions are compared with finite‐element simulation results and measurements on different planar transformers.